1999
DOI: 10.1126/science.285.5433.1533
|View full text |Cite
|
Sign up to set email alerts
|

Postdoctoral Patterns, Career Advancement, and Problems

Abstract: Postdoctoral appointments can have different functions and meanings, depending on the field and whether the postdoc is a man or a woman. The Ph.D.'s-Ten Years Later study confirmed that in biochemistry, the postdoc, not the Ph.D., has become the general proving ground for excellence both in academia and industry. Because they spent a longer time in these "mandatory" postdocs, biochemists had the largest proportion of untenured faculty 10 to 13 years after the Ph. D. In mathematics, where substantially fewer po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(103 citation statements)
references
References 0 publications
6
96
0
1
Order By: Relevance
“…In a smaller proportion of cases, adviser status and interpersonal attraction were also decision criteria. 10 These results closely coincide with those of prior surveys of the motivations for postdoctoral adviser choice (Nerad and Cerny 1999 10 Although adviser status was far from a universal concern (only 15% of scholars explicitly stated that they sought an adviser on the basis of his or her prestige), we suspect that this is due to the fact that many individuals in the data set considered only high-status advisers and did not view prestige differences among the very select members in their consideration set to be germane to their decisions.…”
Section: Oral Historiessupporting
confidence: 80%
“…In a smaller proportion of cases, adviser status and interpersonal attraction were also decision criteria. 10 These results closely coincide with those of prior surveys of the motivations for postdoctoral adviser choice (Nerad and Cerny 1999 10 Although adviser status was far from a universal concern (only 15% of scholars explicitly stated that they sought an adviser on the basis of his or her prestige), we suspect that this is due to the fact that many individuals in the data set considered only high-status advisers and did not view prestige differences among the very select members in their consideration set to be germane to their decisions.…”
Section: Oral Historiessupporting
confidence: 80%
“…Previous work has demonstrated that outputs during the postdoctoral period can be affected by environmental factors (Felisberti and Sear, 2014), as well as by gender (Borrego et al, 2009). The number and duration of postdoctoral appointments also varied by discipline: a decade post-PhD, biochemists represented the largest proportion of untenured faculty out of six mathematics-based disciplines (Nerad, 1999). In recent years the average age of a funded investigator has steadily increased, from 39 in 1980 to 51 in 2008 for the National Institute of Health in the United States; the average age of a new investigator increased from 36 to 42 over the same period (Matthews et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hanchane and Recotillet (2003) demonstrate that going through a postdoctoral program could increase the probability of being recruited as a researcher in the public sector by around 10%. Nerad and Cerny (1999) report that "for mathematics postdocs, the time invested in a postdoc significantly improved the odds of gaining a faculty position." Our estimate (i.e., the marginal effect) is about 2.2% when the endogeneity problem is not taken into consideration (in Model 1 and Model 2 of Table 6).…”
Section: Does Postdoctoral Experience Lead To An Academic Career?mentioning
confidence: 99%
“…In particular, Horta (2009) points out that the reason why postdoctoral experience brings benefits in terms of advancing to academia may be due to the greater research output of academics which is fostered in a postdoctoral position. Engaging as a postdoc is usually seen as a necessary step or a required probation period in order to have sufficient training to obtain an academic position, just like an apprenticeship in some other fields, such as the life sciences or biochemistry (Nerad and Cerny, 1999;Stephan and Ma, 2005;Recotillet, 2007;NPA, 2011). From a social capital perspective, the postdoctoral position provides opportunities to expose those with PhD degrees to more professional networks (Su, 2013).…”
Section: Human/social Capital Theorymentioning
confidence: 99%
See 1 more Smart Citation